PENERAPAN SISTEM AKUNTANSI KEUANGAN DAERAH DALAM MENINGKATKAN INTEGRITAS LAPORAN KEUANGAN PEMERINTAH DAERAH - Rasyid, Rahmawita; Sumarlin, Sumarlin; Fadhilatunnisa, Della (ISAFIR: Islamic Accounting and Finance Review, 2024)
Abstract,This study aims to investigate the implementation and form of local financial accounting systems in enhancing the integrity of local government financial reports. The research method used is qualitative with a phenomenological approach, utilizing primary data from interviews and observations as well as secondary data. The study was conducted at the Office of Community Empowerment and Village Affairs of Gowa Regency, South Sulawesi Province. The results of this study illustrate how the local financial accounting system can enhance the integrity of financial reports through financial management information system (FMIS) and Local Government Information System (SIPD), which provide features that assist in financial management from planning to reporting. The issuance of LAKIP by the Community Empowerment Office also contributes to the transparency and accountability of local government. The Gowa Regency Government has achieved an unqualified opinion for the 11th consecutive time, demonstrating compliance with accounting and financial standards. The implications of this research emphasize that local financial accounting systems can support the integrity of financial reports by focusing on efficiency and effectiveness to prevent manipulation of financial statements..